THE ROLE OF TRADITIONAL JUSTICE PROVIDERS IN IMPLEMENTING THE CUSTOMARY COURT OF ACEH - Nurdin MH; Muazzin Muazzin; Zainal Abidin (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2023)
Any case arising from society could cause disharmony and inbalencing among the society. Taking the case to formal court, will take time, and spend money. The solution to overcome the number of cases in formal court, it needs to set up informal court wellknown “Peradilan Adat”. A lot of cases arising from society in Aceh rural area settled by Aceh Customary Institution Court which is called Peradilan adat Aceh. There are eighteen cases under competency of the court that conducted by justice providers, consist of head of village, Islamic sholars, and other trusted public figures. Dispute settlement run based on both parties consensus voluntarily. Therefore, the decision is “win win solution”. The nature of decision (verdict) is final and binding. Provincial Police institution of Aceh, which is called POLDA, and Aceh Customay Assembly have an MoU signing in order to recoqnize and respect the decision of Customary Court of Aceh.